Implementasi Akad Mudharabah pada Produk Tabungan di BPRS Harta Insan Karimah (HIK) Parahyangan - Jumriati, Jumriati; Kamaruddin, Kamaruddin; Possumah, Bayu Taufik; Majid, Jamaluddin; Wawo, Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to evaluate the implementation of the mudharabah contract in savings products at BPRS HIK Parahyangan for the 2021–2023 period, focusing on the suitability of contract practices with sharia principles, compliance with OJK regulations, and identification of opportunities and challenges in its implementation. The research data consists of primary and secondary data. Primary data were obtained through interviews with management and customers, while secondary data were sourced from the bank's annual report and financial statements, internal documents, DSN-MUI Fatwa No. 02/2000, and POJK No. 19/2014. Data analysis was conducted using content analysis, comparative descriptive analysis, and data triangulation to ensure the validity of the findings. The results show that mudharabah savings are run in accordance with sharia principles and OJK regulations, although still facing obstacles in ratio transparency, income fluctuations, and customer financial literacy. Overall, the mudharabah contract has the potential to be a strategic instrument for BPRS in supporting the development of MSMEs through sharia finance.